Conforto térmico humano em caminhos disponíveis ao uso da bicicleta em Balneário Camboriú - SC, em situação veranil - Writzl, Luana (2022)
This research aims at comprehending the level of human thermal (dis)comfort in relation to the different microclimates present in the surroundings of Balneário Camboriu’s bikeways in the summer. To that aim, a systematic review was conducted to identify the existing publications that could comply with the research topic. Later, a characterization of the urban morphology in the area of interest was conducted using Local Climate Zones and Sky View Factor, in order to contribute to the choice of routes to be traversed through the existing bikeways, at 9 a.m. and 4 p.m. in two different days, with meteorological equipment attached to the bicycle. The thermal comfort in the summer was evaluated using the Physiological Equivalent Temperature (PET) and Universal Thermal Climate Index (UTCI) indexes. The results showed that at 9 a.m. there is a greater tendency of thermal discomfort at the eastern part of the city and that the the values diminish at the western part, whereas at 4 p.m. the opposite occurs regardless of haziness. Thermal comfort was only observed at 4 p.m. in both days; at January 11th 2022, only the UTCI showed comfort at this hour, in 58% of the pathways. At January 14th 2022, the PET index showed that 24% of the pathways were comfortable, whereas the UTCI showed that 100% of them were thermally comfortable at 4 p.m. The data obtained from these mobile measurements, together with the data about structure, position and urban (im)permeability gave the groundings to comprehend the human thermal (dis)comfort estimated from the interpretative ranges of PET and UTCI for subtropical climates.